If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12+2c+9c-6-11c=0
We simplify the equation to the form, which is simple to understand
12+2c+9c-6-11c=0
We move all terms containing c to the left and all other terms to the right.
+2c+9c-11c=0-12+6
We simplify left and right side of the equation.
c=-6
0=-6
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 12y+3=7 | | b^2-8b-58=0 | | -4n+3-7n= | | 15y-6=11 | | 8-5+j=67 | | 9y=3y | | 25w^2-x^2=0 | | -12+8m-6+1=1+5m+6m | | -12+8m-6+1=1+5m+6 | | -286+88= | | 1=x-1 | | 6r^3+15r^2-6r= | | 6y^2+3y-18=0 | | -10+8k=3k-5 | | 2x+4(0)=8 | | x=4x+12 | | 8-2(x+5)=4(2x-1) | | 5x-1=4x+9 | | 8(5n+7)=216 | | 4=p-2 | | -5+x=-3 | | 16=4a+8+4a | | 6x+4=2(x-6) | | 8a^2-4d=60 | | 15x-7x=-52-5x | | 12x^2-33x+18=0 | | 8y^2+26y=-15 | | 5m+1-8m=22 | | 1m/9+10=16 | | M+4=20+3m | | 10x-35=5x+25 | | 3(4k+8)-2(2k+3)-14k= |